Becoming the Denigrated Other: Group Relations Perspectives on Initial Reactions to a Bipolar Disorder Diagnosis - Goldberg, Susan G. (Frontiers in Psychology, 2012)
The initial reactions to a bipolar disorder diagnosis of research participants in a small, qualitative study consisted of astonishment, dread of being “mad,” and extremely negative associations. All had prior mental health diagnoses, including episodes of severe depression (all but one) and alcoholism (one). All participants reported mental health histories prediagnosis and most had spent years contending with mental health labels, medications, symptoms, and hospitalizations. In addition, most participants were highly educated health professionals, quite familiar with the behaviors that the medical system considered to comprise bipolar disorder. Their negative associations to the initial bipolar disorder diagnosis, therefore, appeared inconsistent with their mental health histories and professional knowledge. This article contextualizes these initial reactions of shock and distress and proposes interpretations of these findings from societal and psychodynamic group relations perspectives. The participants’ initial negative reactions are conceptualized as involving the terror of being transported from the group of “normal” people into the group of “mad” or “crazy” people, i.e., people with mental illnesses, who may constitute a societal “denigrated other.”